How Does Creative Arts Therapy Reduce Distress for Children With Cancer? A Metasynthesis of Extant Qualitative Literature. (March 2020) - Raybin, Jennifer L.; Barr, Emily; Krajicek, Marilyn; Jones, Jacqueline
Introduction: As more children survive cancer, attention must be paid to their quality of life (QOL). Integrative therapies are an ideal modality for nurses to advocate for reducing distress and improving QOL for children with cancer. Creative arts therapy is a type of integrative health that may improve QOL in this population. Therefore, the research question was asked, "For children with cancer, what opportunities exist for creative arts therapy to reduce distress?"Method: A metasynthesis of the extant qualitative research was conducted to answer the research question. Seven qualitative studies were identified, which included 162 participants. New themes were identified through rigorous analyzation by the study team of each study as individual data.Results: Four derived analytic themes emerged through the analysis: (a) connection is established through creative expression, (b) coping is facilitated by creative arts, (c) communication is enabled by creative arts interventions, and (d) continuance (the concept of time) is experienced through creative arts. Examples of each theme with subthemes are delineated, including expressive quotes.Summary: Through this qualitative synthesis of studies with creative arts therapy, evocative opportunities to reduce the distress associated with the disease experience are revealed. Nurses are called now to promote creative arts therapy to improve the symptoms in children with cancer.